Microfinance in Mongolia - Turbat, Batbayar (2008)
During the economic and political transition, Mongolia suffered from high structural unemployment. Therefore the government of Mongolia implemented the National Poverty Alleviation Program which aimed at poverty alleviation through encouraging the establishment and development of the micro entrepreneur activities. This above all required easy and affordable access to financial services. Microfinance is described as a broad range of financial services such as deposits, loans, payment services, and insurance to the poor and low-income households and micro-enterprises. Using methodologies, which are unique to it, microfinance aims at supporting entrepreneurial activities and improving the living standard of these households